Smart Battery Management Systems and Comprehensive Comparison of Batteries for Electric Vehicles (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The automotive industry has a strong demand for electric vehicles because of their exceptional ability to compete with internal combustion engines. In any electric car, batteries are an essential part. They basically act as the heart of the car. Controlling the battery system can significantly speed up the creation of an electric vehicle. Our study and research provide insight into the present battery scenario, namely Lithium-ion batteries, which are currently driving the era. Nonetheless, there are superior alternatives to lithium-ion batteries due to their variable downsides. Flow batteries are a worthy competitor to Li-ion batteries, as they give various advantages over current conventional batteries. The study also covers the benefits and advancements of batteries for high-voltage applications. Our research examines the replacement of Li-ion batteries with Vanadium redox flow batteries and analyses the results to support the decision to employ flow batteries. The flow batteries will significantly enhance electric vehicles.